Assessment of Cluster and Network Collaboration Influence on Regional Economy - KAMENSKIKH, Mariia (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
In view of the specified current trends of world economy development, which initiate generation functioning of a new type on the basis of the network concept, it is necessary to consider features of interaction of regional economy subjects in the context of cluster and network collaboration, as well as the concept of knowledge economy. This article is devoted to the research of the cluster and network collaboration importance in the region in the context of economic and innovative development. The main attention is paid to research universities, enterprises and authorities’ interactions, as these institutes are the main in the knowledge generation and commercialization processes through R&D, financing, state programs, etc. Based on the theory of network regional interaction, creation of the theoretical and mathematical models, which are reflecting influence of cluster and network interaction on the level of economic development, seems possible. Results of the modeling confirm a hypothesis about positive influence of cluster and network collaboration by regional economic development. Significant influence of the number of graduates and post-graduate students, R&D expenses and capital formation on GRP is revealed. This research might be used for working out management instruments for regional development.